Une Etude Exploratoire De La Politique D’ouverture Du Capital Aux Salariés Dans Les Entreprises Au Cameroun - Ousmanou Alim (European Scientific Journal, ESJ, 2016)
The purpose of this work is to examine the employees ownership policy in Cameroon’s companies. The information used is derived from primary data collected between November 2015 and January 2016 in 31 Public Limited Companies having opened the capital to their employees. They belong to all sectors: industry, service, agriculture, transport and trade. From the perspective of the workforce of employees, these companies are mostly large (employing more than 100 employees) and medium (employing between 20 and 100 employees). Through exploratory factor analysis and the univariate analysis, the study reveals that there are two forms of share ownership by employees in these companies: the direct form and indirect form. Similarly, the level of participation of employees in the capital of these enterprises is usually between 5% and 10% and the average level of around 7.4% . The privatization of public and para-public enterprises was a major factor of the opening of capital to employees in the firms of the sample. In addition, the establishment of global employee share plan in subsidiaries of foreign companies is also one of the reasons attached to this policy. As for the benefits of implementing this policy, they are among others the improvement of productivity, economic performance and social performance of these companies.